Exploring the impact of digital financial inclusion on sustainability: A bibliometric analysis of emerging research trends - Ranjitha, C R; Prasad, Kushini (The International tax journal, 2026)
The Current Research Explore the influence of digital financial inclusion in achieving sustainable development. Through expanding its access to financial services where it supports the United Nations’ Sustainable Development Goals (SDGs). This study adopted a bibliometric approach to analyze the literature review on digital financial inclusion and its role in sustainable development pub lished between 2016 and 2024. Data is obtained from the Scopus database; after the screening process, it yielded 833 relevant documents. The study also used descriptive analysis to explore year-wise trends and prominent countries and top authors. The bibliometric study identified keyword clusters and co-authorship networks. The result shows strong publication growth after 2019, with China, the United Kingdom, and India as leading contributors. And five thematic clusters using VOSviewer software were recognized, covering finance–sustainability linkages, environmental and economic impacts, technological enablers, advanced digital technologies, and policy governance. However, co-authorship networks continue as fragmented, dominated by small regional groups. This study provides future researchers with a clear map of the existing literature and gaps that can give direction on qualitative and empirical studies.